Beyond Neoliberalism? Crisis and the Prospects for Progressive Alternatives - Cahill, Damien (New Political Science, 2011)
The onset of the current global economic crisis was hailed by many as signalling the demise of neoliberal hegemony. Two years on however, neoliberalism appears to be quite durable. Indeed, after a brief period of Keynesian-type responses, states, on the whole, have embraced neoliberal solutions to the fiscal problems generated by the crisis. Greece, for example, is now following an IMF programme of privatisation and cuts to social expenditure, while other European nations are pursuing austerity policies. In the USA, state and municipal governments are selling off public assets in response to mounting deficits. This paper explains the durability of neoliberalism and the opportunities and challenges it creates for non-neoliberal progressive policy agendas. Drawing upon Karl Polanyi's conceptual framework, this paper argues that neoliberalism is best understood as a historically specific process of state and economic restructuring that is socially embedded through three mechanisms: ideological norms, class relations, and institutional rules. This paper examines responses by states to the crises and concludes that, although the ideological legitimacy of neoliberalism has been somewhat weakened, there is little evidence to suggest that the three mechanisms, through which neoliberalism is socially embedded, have been significantly eroded. The implication for progressive politics is that, just as neoliberalism is socially embedded, so would a successful progressive non-neoliberal political programme need to be socially embedded: through the articulation of a coherent alternative ideology; through the mobilisation of social forces; and through the institutionalisation of non-neoliberal rules and norms within the apparatuses of the state.
Keywords: Keynesian economics; economic policy; global financial crisis, 2008-2009; neoliberalism; progressivism; social embeddedness

Polanyi and Post-neoliberalism in the Global South: Dilemmas of Re-embedding the Economy - Sandbrook, Richard (New Political Economy, 2011)
Although Karl Polanyi Studied a different epoch and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era. The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi's reflections on progressive alternatives to liberalism clarify contemporary debates on development alternatives in the Global South? I contend that democratic socialism – Polanyi's preferred remedy to the ‘demolition’ of society and nature occasioned by market civilisation – is problematical in light of what we have learned from the twentieth century, but his framework for evaluating alternatives – featuring the re-embedding of economy in society – remains as powerful as ever, I support this argument with an exploration of socialism and social democracy – as well as community – based alternatives arising from ‘reciprocity’. Each possibility raises distinctive dilemmas, as an analysis of cases reveals.
Keywords: Global South; communitarianism; development alternatives; global south; globalisation; globalization; political economy; post-neoliberalism; social democracy; socialism

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; TONNIES, Ferdinand, 1855-1936; WEBER, Max, 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Conceptualizing the Economic Role of the State: Laissez-Faire, Technocracy, and the Democratic Alternative - Sabeel Rahman, K (Polity, 2011)
This article contrasts three visions of political economy that appear in the writings of Keynes, Hayek, and Polanyi, and discusses their relevance to current debates over economic policy in the United States. Keynes proposed optimizing market practices through technocratic governance. In recent decades, this influential approach has proven vulnerable to the revival of Hayek's laissez-faire arguments. Polanyi, by contrast, introduced a framework that criticizes both laissez-faire conceptions and the technocratic approach pioneered by Keynes. Because of its emphasis on democratic participation, Polanyi's reasoning provides the building blocks for a new type of contemporary progressive politics.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; United States; economic policy; free enterprise; government regulation; progressivism; the state

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Keywords: capitalism; double transformation; socialism; solidarity economy

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Keywords: positivism; religion; social sciences; socialism

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Keywords: capitalism; emancipation; feminism; gender; welfare state

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Karl Polanyi And The Great Transformation - Örmeci, Ozan (Sosyal Bilimler Dergisi, 2011)
Özet: 20. yüzyılın önde gelen iktisatçılarından olan Karl Polanyi (1886-1964), Büyük Dönüşüm adlı eserinde ortaya koyduğu özgün tezler ile halen kapitalizme en ciddi eleştiriyi getirmiş kişilerden biri kabul edilmektedir. Polanyi'nin klasik ENG: Karl Polanyi is known as one of the most famous economists of the world who strongly criticized liberalism and the idea of self-regulating market. Polanyi’s masterpiece The Great Transformation is still accepted as one of the most powerful critiques of liberal economics and many writers from different political backgrounds refer to this book while criticizing the dominant liberal economic understanding. The Great Transformation is a very rich and complex book in which Polanyi analyzes the evolution of the free-market ideology and the counter movement against the damages of liberal economics. Although Polanyi called himself as a socialist, his ideas are very dense and it is not easy to label him as a defender of certain ideology.
Keywords: Great Transformation, The (Book); review

Towards a Neo-Polanyian Political Economy of Development - Sandbrook, Richard (Conference Papers -- International Studies Association, 2011)
The Global South has entered an era of ideological flux. The inadequacies of neoliberalism have spawned a widespread questioning of this dominant worldview. Intellectuals and political movements search for an alternative development ideology that explains what has gone wrong, provides a vision of a more desirable future and suggests a process for achieving this goal. Responding to these challenges, the World Bank and other purveyors of the dominant model have undertaken a gradual shift from an unpopular and inefficacious “Washington Consensus” to a more complex and politically progressive “Post-Washington Consensus”. This shift, though blunting the attack on neoliberalism, has moved the debate on legitimate development strategies to the left and towards more statist approaches. Socialism, the developmental state, social democracy, and emancipatory community-based development have moved back into development discourse. In an earlier era of ideological flux, Karl Polanyi probed the origins of the implosion of economic liberalism in the Great Depression and two world wars, as well as the alternatives that might, by re-embedding the economy in society, allow people to live freer and more secure lives. These reflections came together in The Great Transformation, his masterwork that appeared in 1944. Although Polanyi studied a different era (1830-1940) and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era (since 1980). The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi’s reflections on progressive alternatives to liberalism clarify contemporary debates on progressive alternatives to neoliberalism in the Global South?
Keywords: Global South; World Bank; economic development; global south; ideology; political movements; social democracy; socialism